2020
DOI: 10.1002/met.1949
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Amazon floods to modes of climate variability: A review

Abstract: Anomalous conditions in the oceans and atmosphere have the potential to be used to enhance the predictability of flood events, enabling earlier warnings to reduce risk. In the Amazon basin, extreme flooding is consistently attributed to warmer or cooler conditions in the tropical Pacific and Atlantic oceans, with some evidence linking floods to other hydroclimatic drivers such as the Madden-Julian Oscillation (MJO). This review evaluates the impact of several hydroclimatic drivers on rainfall and river dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 174 publications
(304 reference statements)
0
29
0
1
Order By: Relevance
“…A global daily reanalysis of river discharge is provided at a resolution of 0.1 • (∼ 32 km) for the 36-year analysis period . The data are derived from the operational Global Flood Awareness System, version 2.1 (GloFAS; Alfieri et al, 2013;Harrigan et al, 2020), where runoff output from the H-TESSEL module of the European Centre for Medium-Range Weather Forecasts (ECMWF), integrated forecast system (IFS; cycle 41r2), is coupled to the calibrated LISFLOOD routing model (van Der Knijff et al (2010); see Hirpa et al (2018) for details on calibration) to produce deterministic estimates of historic river flows. All of the 58 stations were used within the calibration of Lisflood.…”
Section: Glofas 21 River Flow Reanalysismentioning
confidence: 99%
See 1 more Smart Citation
“…A global daily reanalysis of river discharge is provided at a resolution of 0.1 • (∼ 32 km) for the 36-year analysis period . The data are derived from the operational Global Flood Awareness System, version 2.1 (GloFAS; Alfieri et al, 2013;Harrigan et al, 2020), where runoff output from the H-TESSEL module of the European Centre for Medium-Range Weather Forecasts (ECMWF), integrated forecast system (IFS; cycle 41r2), is coupled to the calibrated LISFLOOD routing model (van Der Knijff et al (2010); see Hirpa et al (2018) for details on calibration) to produce deterministic estimates of historic river flows. All of the 58 stations were used within the calibration of Lisflood.…”
Section: Glofas 21 River Flow Reanalysismentioning
confidence: 99%
“…The impact of different climatic phases tends to cause a similar response for both rainfall and river discharge (Towner et al, 2020), though the relationship between flooding and rainfall can be non-linear (Stephens et al, 2015;Coughlan de Perez et al, 2017) with significant differences identified between the mean state of the two variables in response to the same climate phase (Dettinger and Diaz, 2000). An example of this for the Amazon is detailed by Marengo et al (2012) in a comparison study of the 1989, 1999 and 2009 floods, whereby the worst flood event did not correspond with the largest rainfall anomaly (mm −1 d −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Amazon basin, while the literature has described relationships between climate patterns and hydrometeorological variables, the way in which climate variables influence flood risk remains understudied (Towner et al, 2020) as a result of the nonlinear relationship between precipitation and streamflow (Stephens, Day, Pappenberger, & Cloke, 2015).…”
Section: Hydroclimatology Of Perumentioning
confidence: 99%
“…Numerous hydroclimatic drivers have been identified to cause anomalous rainfall and river discharge conditions in the Amazon basin (Towner et al, 2020), with ENSO and tropical Atlantic SST variability considered to be the most influential (Marengo et al, 1992;Ronchail et al, 2005b;Yoon and Zeng, 2010;Espinoza et al, 2019). Several indices of ENSO are available, differing on spatial location, variable type and on the number of variables used.…”
Section: Hydroclimatic Drivers and Modes Of Variabilitymentioning
confidence: 99%
“…The impact of different climatic phases tends to cause a similar response for both rainfall and river discharge (Towner et al, 2020), though the relationship between flooding and rainfall can be non-linear (Stephens et al, 2015;Coughlan de Perez et al, 2017), with significant differences identified between the mean state of the two variables in response to the same climate phase (Dettinger and Diaz, 2000). An example of this for the Amazon is detailed by Marengo et al (2012) in a comparison study of the 1989, 1999 and 2009 floods, whereby the worst flood event did not correspond with the largest rainfall anomaly.…”
Section: Introductionmentioning
confidence: 99%